Penggunaan Metode Hiwar untuk Meningkatkan Penguasaan Kosa Kata Bahasa Arab pada Siswa Kelas V MIN 4 Medan - Habibah Khairani; Robbi Reyhan Chandra; Tria Wulandari; Sari Annisa Siregar; Sakholid Nasution (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to improve the mastery of Arabic vocabulary in fifth grade students at Madrasah Ibtidaiyah Negeri Medan 4 through the application of the hiwar (conversation) method. The hiwar method involves students in direct conversational practice using the vocabulary learned. This research is classroom action research using qualitative methods with an enographic approach and data collection techniques using observation, interviews and documentation.  The research results showed that the initial condition of students' vocabulary mastery was low, with only 46% of students reaching the minimum completeness criteria. After implementing the hiwar method, there was a significant increase in vocabulary mastery, with 75% of students achieving completion in the second cycle. The use of interesting and varied learning media also contributes to increasing student interest and motivation in learning. This research concludes that the hiwar method supported by appropriate learning media can increase students' mastery of Arabic vocabulary effectively.